Evaluation of filter paper calibrations for indirect determination of soil suctions of an unsaturated compacted silty sand - Bicalho, Kátia Vanessa (2009)
The soil suction is a key variable in the analysis of the hydro-mechanical behavior of unsaturated soils. The filter paper method (FPM) calculates soil suction indirectly by measuring the gravimetric water content of the filter paper at equilibrium that is related to soil suction through a predetermined calibration curve between the water content of the filter paper and suction. This paper evaluates the use of six published calibration functions for the Whatman 42 filter paper for indirect determination of soil suctions of an unsaturated compacted silty sand. Evaluation of the filter paper calibrations was carried out using the experimental results given by Fleureau et al. (2002) obtained with other techniques used to measure or control the soil suctions in the compacted silty sand. The results show that the matric suctions inferred from FPM depend on the used calibration function. A modified calibration function is suggested, which gives better estimation of the soil water retention curve for the investigated soil. The FPM offers a promising simple technique for the determination of soil suction, provided that an adequate calibration function is used for the investigated soil saturation range.